2022
DOI: 10.1177/02692155221079117
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture-related treatments improve cognitive and physical functions in Alzheimer's disease: A systematic review and meta-analysis of randomized controlled trials

Abstract: Objective To determine acupuncture-related treatments’ effects and duration on improving cognitive function, physical function, and quality of life in patients with Alzheimer's disease. Data sources Eight electronic databases were searched for eligible randomized controlled trials from database inception to January 2021, including Medline, PubMed, EBSCO, Embase, Cochrane, Airiti Library, China National Knowledge Infrastructure, and China Journal Full-text Database. Review methods A systematic review and meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…EA has been recognized as a crucial treatment in traditional Chinese medicine (TCM), which applies the inserted needles with an electric stimulating current to the acupoints. Clinical trials have shown that EA-treatment improved cognitive outcomes in early and mid-stage AD patients, and notably on memory function in AD prodromal patients (Deng and Wang, 2016;Jia et al, 2017;Lin et al, 2022). A review summarized that EA at acupoints such as Baihui (DU20), Shenting (DU24), and Neiguan (PC6) effectively improve the score of cognitive tests in patients with cognitive impairment, respectively (Yin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…EA has been recognized as a crucial treatment in traditional Chinese medicine (TCM), which applies the inserted needles with an electric stimulating current to the acupoints. Clinical trials have shown that EA-treatment improved cognitive outcomes in early and mid-stage AD patients, and notably on memory function in AD prodromal patients (Deng and Wang, 2016;Jia et al, 2017;Lin et al, 2022). A review summarized that EA at acupoints such as Baihui (DU20), Shenting (DU24), and Neiguan (PC6) effectively improve the score of cognitive tests in patients with cognitive impairment, respectively (Yin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…therapeutic procedure that stimulates acupoints, has been thoroughly researched and used to treat Alzheimer's disease [33]. Acupuncture therapy improved cognitive function in patients with Alzheimer's disease and elderly people with mild cognitive impairment, according to clinical studies and systematic reviews [34][35][36][37][38]. Animal studies have contributed to the discovery of the mechanism by which electroacupuncture protects neurons in Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is an effective therapeutic method, which has been widely practiced in China for more than 2,000 years. Several systematic reviews and meta-analyses have demonstrated that acupuncture can improve symptoms of CNS disorders, and its anti-inflammatory effects have long been proven (Chen et al, 2022b, He et al, 2022Lin C. J. et al, 2022;Zhou Z. et al, 2022). Exhilaratingly, PROKR2 neurons are indispensable for the anti-inflammatory effect of low-intensity electroacupuncture (EA) through the vagal-adrenal axis, which was once again confirmed by the article published in the authoritative journal NATURE last year (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 91%